Em busca de identidades: crianças brasileiras no Japão - Prado, Gisele Silva (2017)
The following study traces an investigation of how the socialization and identity formation are developed in Brazilian kids attending Elementary School in Japan, from the school context, as well as their insertion in the society. The interest for this theme came after confronting this reality for 14 years living at the referred country. According to the Ministry of Foreign Affairs in Brazil, the second biggest Brazilian community abroad, with more than 175 thousands of residents (2015), is located in Japan. In face of such expressive community, and recurrent difficulty of socialization, it is necessary to observe how are developed the relationships between the alien Brazilian kids living in Japan and the society in which they are living, and which are the barriers that hinder the process of socialization and insertion in the community.